Multivariate Adaptability of Tropical Wheat Cultivars to Drought and Salinity Stresses - Alan Mario Zuffo; Jorge González Aguilera; Francisco Charles dos Santos Silva; Ricardo Mezzomo; Leandra Matos Barrozo; Fábio Steiner; Bruno Rodrigues de Oliveira; César Augusto Masgo Soto; Carlos Genaro Morales-Aranibar; Nataniel Linares-Gutiérrez; Luis Morales-Aranibar (Plants)
Wheat production in the Brazilian Cerrado region faces challenges related to drought and salinity, which limit plant development and crop yield. This study evaluated the multivariate adaptability of 11 tropical wheat cultivars to drought and salinity stresses during early plant development. Wheat plants were grown for 12 days at 25 °C under non-stressful (control) and simulated drought and salinity stress conditions with –0.30 MPa iso-osmotic solutions prepared with polyethylene glycol or sodium chloride, respectively. The germination, growth rate and dry matter accumulation of the plants were measured. The results showed that wheat cultivars have distinct morphological responses to stressful environmental conditions, with drought stress having a greater impact on shoot growth and saline stress having a greater impact on root system development. The multivariate adaptability and stability analyses performed using the Lin and Binns method and GGE biplot revealed that the wheat cultivars BIO 190057, BRS 404 and TBIO Duque combine adaptability and stability for all morphological traits simultaneously, being considered cultivars tolerant to drought and salinity stresses. It was concluded that the identification of cultivars tolerant and adapted to adverse environmental conditions is essential for the advancement of sustainable cultivation of tropical wheat in the Brazilian Cerrado region, contributing to global food security.